Complications and patient-reported outcomes after radiotherapy in breast cancer patients undergoing implant-based breast reconstruction: a retrospective study from a large Chinese breast disease center - Tianyi Ma; Teng Ma; Xiangjun Li; Xinyi Sun; Weihong Cao; Zhaohe Niu; Haibo Wang (World Journal of Surgical Oncology)
Abstract Background Postmastectomy radiation therapy (PMRT) can influence the outcome of implant-based breast reconstruction (IBBR). This study aims to investigate the complications and patient-reported outcomes (PROs) following PMRT between direct-to-implant (DTI) and tissue expander-to-implant (TEI) reconstruction. Methods The retrospective study included breast cancer patients undergoing IBBR and PMRT. Patients were divided into a permanent implant group (PI-PMRT) and a tissue expander group (TE-PMRT). Complications, reconstruction failure, and reoperation were compared between the two groups. PROs were assessed using the BREAST-Q scale. Results A total of 203 patients were included: 99 in the PI-PMRT group and 104 in the TE-PMRT group. The incidence of severe capsular contracture was significantly higher in the PI-PMRT group compared to the TE-PMRT group (37.4% vs. 24.0%, p = 0.039). The PI-PMRT group had a significantly lower rate of reconstruction failure (9.1% vs. 19.2%, p = 0.039) and reoperation (13.1% vs. 24.0%, p = 0.046). Multivariate analysis revealed that the absence of mesh (OR = 2.177, p = 0.040) and DTI reconstruction (OR = 1.922, p = 0.046) were independent predictors of severe capsular contracture; the absence of mesh (OR = 4.699, p = 0.015) and TEI reconstruction (OR = 2.429, p = 0.043) were independent predictors of reconstruction failure. BREAST-Q scores indicated greater breast satisfaction in the PI-PMRT group (p = 0.031). Conclusions Although DTI reconstruction resulted in a higher risk of severe capsular contracture, the higher risk of reconstruction failure and reoperation in patients undergoing TEI reconstruction was even more concerning. Furthermore, patients were more likely to report greater breast satisfaction with DTI reconstruction. Therefore, DTI reconstruction may be a more appropriate option for patients anticipating PMRT.